2023
DOI: 10.3324/haematol.2022.281772
|View full text |Cite
|
Sign up to set email alerts
|

Real-world study of the efficacy and safety of belantamab mafodotin (GSK2857916) in relapsed or refractory multiple myeloma based on data from the nominative ATU in France: the IFM 2020-04 study

Abstract: Belantamab mafodotin (BM) is an anti-BCMA antibody-drug conjugate (GSK2857916) that represents an alternative option in multiple myeloma. We sought to assess the efficacy and safety in real-world of BM in patients who benefited from an early access program. We conducted an observational, retrospective, multicenter study. Eligibility criteria were treatment of relapsed or refractory multiple myeloma (RRMM) in monotherapy in adult patients who have received at least 3 lines of therapy previously, including at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…The survival outcomes were more favorable for the responders, most of whom had sustained disease control and long-term remission. Accumulating evidence from real-world studies is in accordance with our results (Table 2) [14][15][16][17][18][19]. A multicenter Italian study had a comparable cohort size (n = 28) to our study and reported an ORR of 40% and comparable survival outcomes [15].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The survival outcomes were more favorable for the responders, most of whom had sustained disease control and long-term remission. Accumulating evidence from real-world studies is in accordance with our results (Table 2) [14][15][16][17][18][19]. A multicenter Italian study had a comparable cohort size (n = 28) to our study and reported an ORR of 40% and comparable survival outcomes [15].…”
Section: Discussionsupporting
confidence: 90%
“…A multicenter Italian study had a comparable cohort size (n = 28) to our study and reported an ORR of 40% and comparable survival outcomes [15]. In France, the IFM reported the outcomes of the compassionate use program of belantamab mafodotin including 97 patients with a median of five prior lines of therapies [17]. However, only 56% of the patients were triple-class refractory in this cohort.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The antitumor activity of belantamab mafodotin was corroborated in an observational, retrospective, multicenter study in 106 adult patients with heavily pretreated RRMM. 39 Approximately half of the patients were tripleclass refractory and 11.3% were penta-class refractory. Approximately 38.0% of patients had an overall response, with a median DoR of 9 months.…”
Section: Bcma-directed Antibodies Belantamab Mafodotin: Adc Therapy F...mentioning
confidence: 99%